Community Structure of Fish and Environmental Characteristics in Cisadea River, West Java, Indonesia - Epa Paujiah; Dedy Duryadi Solihin; Ridwan Affandi (Jurnal Biodjati, 2019)
Environmental characteristics can influence the distribu-tion of animal communities including fish in aquatic habitats such as a river. The study of fish communities in Cisadea River aimed to learn the relation between the fish community structure and the environmental characteristics of the river itself. This research was conducted in Cisadea River, Cianjur Regency, West Java, Indone-sia during dry season from July 2012 until February 2013. Samples of fish were caught using active fishing gear (Electrofishing Gear, spreading nets, scoop, lift net) and passive fishing gear (trap). The results showed that the quality of the physical chemistry of Cisadea waters was still in the normal range that could support fish life. The fish community in Cisadea River consisted of 11 orders, 26 families, 35 genera and 48 species. During the study, Rhyacichthys aspro (19,85%) and Glyptothorax plathypogon (20,15%) were the domi-nant species caught. The diversity index value (H’) was 2.87 (mid-dle category) with the dominance value of 0.09 (low category) and evenness value of 0.74 (high category). Moreover, community simi-larities according to the presence of species made the LC1 and LC2 locations in one group while the LC3 locations in a separate group.